Strategies for Maintaining Tax Compliance of SMEs During Covid-19 Pandemic by Using Supply Chain Management Integration Approach - Aramia Fahriyah; Wuwuh Andayani; Rochland Yoseph; S. Penta Nurwibowo; Wendy Irawan (Ilomata International Journal of Tax and Accounting, 2022)
The new normal life of Covid-19 pandemic has brought a new life pattern which is more strict health protocols in the interaction among each other. In the normal time, although the level of tax revenue shows a rising trend, the tax ratio hasn’t shown any significant increase. Also, it is still left behind other developing countries. Related to the pandemic effect, the world economy is decreasing and resulting to the decline of the Indonesian tax revenue. The concerns of this study are on how to optimize the compliance level of tax payment from Small-Medium Sized Enterprises (SMEs) and the efforts of optimization needed to be done including in helping SMEs for being able to survive and or to be improved in terms of its business performance. Thus, they can contribute to maintaining their tax compliance at the same time from getting worse. This study employed a descriptive research method using a qualitative approach. The data sources were primary and secondary data. In this study, an operational management tool which is the approach of Supply Chain Management (SCM) integration will be implemented as the solution. It is found that the gradual application of the concept of SCM integration will give several significant impacts on the SMEs’ performance including their compliance with the existed tax regulations. Also, this will encourage the optimal taxation authority in managing the tax participation of the SMEs sector.